α,25(OH)2D3 promotes oxidative stress in endothelial cells transformed by vGPCR - Tapia, Cinthya Mariela (2021)
The infectious cause of Kaposi’s sarcoma (KS) neoplasm is KS-associated Herpesvirus (KSHV or human herpesvirus 8). Furthermore, virally G Protein-coupled Receptor (vGPCR) is one of the molecules from the lytic phase able to induce KS-associated cellular modifications through paracrine oncogenesis. We have previously demonstrated that 1α,25(OH)2D3 exerts antiproliferative effects on endothelial cells that stably express vGPCR by inhibiting NF-κB pathway and promoting apoptosis and autophagy. Oxidative stress is frequent in many types of cancer where reactive oxygen species (ROS) can act as a promoting or suppressing agent. In this work, our goal was to study the involvement of ROS as part of the antineoplastic mechanisms triggered by 1α,25(OH)2D3 in vGPCR cells. By a spectrofluorimetric method using the H2-DCF-DA probe, ROS levels were detected higher than control conditions after 1α,25(OH)2D3 (10 nM, 24 or 48 h) treatment. When VDR expression was knocked down by shRNA against VDR (vGPCR-shVDR cell line), ROS increase was found to be VDR dependent (48 h). Our previous reports indicated that vGPCR cells proliferation decreases at 80% after 1α,25(OH)2D3 treatment, triggering cell cycle arrest and apoptosis by a mechanism dependent on the caspase-3 cleavage. In this case, Western blot studies showed an increase expression of pro-apoptotic proteins like BIM and caspase-3 cleavage by 1α,25(OH)2D3 (10 nM, 48 h) and no reversal effect by N-Acetyl-cysteine (1 mM) antioxidant was observed. Altogether, these preliminary results suggest that ROS levels promotion by 1α,25(OH)2D3 through VDR, triggers apoptosis-related mechanisms on vGPCR cells.